2016
DOI: 10.5194/acp-16-1255-2016
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of VIIRS, GOCI, and MODIS Collection 6 AOD retrievals against ground sunphotometer observations over East Asia

Abstract: Abstract. Persistent high aerosol loadings together with extremely high population densities have raised serious air quality and public health concerns in many urban centers in East Asia. However, ground-based air quality monitoring is relatively limited in this area. Recently, satellite-retrieved Aerosol Optical Depth (AOD) at high resolution has become a powerful tool to characterize aerosol patterns in space and time. Using ground AOD observations from the Aerosol Robotic Network (AERONET) and the Distribut… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
70
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(79 citation statements)
references
References 27 publications
7
70
2
Order By: Relevance
“…2017, 9, 403 5 of 13 [17]. However, this result was inconsistent with a previous validation study, in which 32% of VIIRS IP retrievals fell into the EE, with a slightly low R 2 of 0.63, and a relatively large positive bias (0.25) in Beijing within 3 km around AERONET [24]. The different aerosol types may have caused this difference between Beijing and Wuhan.…”
Section: Comparison and Verification Of Methodscontrasting
confidence: 56%
See 1 more Smart Citation
“…2017, 9, 403 5 of 13 [17]. However, this result was inconsistent with a previous validation study, in which 32% of VIIRS IP retrievals fell into the EE, with a slightly low R 2 of 0.63, and a relatively large positive bias (0.25) in Beijing within 3 km around AERONET [24]. The different aerosol types may have caused this difference between Beijing and Wuhan.…”
Section: Comparison and Verification Of Methodscontrasting
confidence: 56%
“…According to suggestions from other research groups [16,22,24], data matching was performed with the following rules. First, the mean AOD was averaged when at least 20% of the pixels fell within the sampling box.…”
Section: Comparison and Verification Of Methodsmentioning
confidence: 99%
“…Because it has more channels with higher spatial resolution in the visible and near-infrared (NIR) bands compared with recent and planned advanced meteorological sensors in GEO, including the Advanced Himawari Imager (AHI), the Advanced Baseline Imager (ABI), and the Advanced Meteorological Imager (AMI), GOCI provides valuable information related to AOPs. Hourly AOD from the GOCI YAER algorithm is in good agreement with Moderate Resolution Imaging Spectroradiometer (MODIS) and Visible Infrared Imaging Radiometer Suite (VIIRS) AOD over East Asia (Xiao et al, 2016). The application of GOCI retrievals through data assimilation results in improved performance of several air quality forecasting model predictions of AOD and PM concentrations (Park et al, 2014;Saide et al, 2014;Jeon et al, 2016;Lee et al, 2017).…”
mentioning
confidence: 68%
“…They also concluded that the merged product does not specifically outperform the DT or DB results. The Terra C6 3 km AOD product was validated by Xiao et al (2016) using AERONET data from the DRAGON Asia campaign (2012-2013) (Holben et al, 2017) and over Beijing using hand-held sun photometers. Tao et al (2015) evaluated MODIS/Aqua C6 AOD over different regions in China for both DB and DT products, but not for the merged DTDB AOD, using AERONET data as reference.…”
Section: Modis C51 Vs C6mentioning
confidence: 99%
“…Xu et al, 2015;Ma et al, 2016; but also using multiple satellite data (Lin et al, 2010;Guo et al, 2011Guo et al, , 2016bDong et al, 2017;Zhao et al, 2017;Zhang et al, 2017). However, these studies used MODIS C5.1 AOD data and substantial differences exist between C6 and C5.1 (e.g., Levy et al, 2013;Sayer et al, 2014;Tao et al, 2015;Xiao et al, 2016). Furthermore, in addition to data sets over dark and brighter surfaces from the DT and DB algorithms, respectively, C6 also provides a merged DTDB data set based on criteria using the quality flags in each product .…”
Section: Introductionmentioning
confidence: 99%